From Alienation to Irony: Critical Film Studies and Kynical Subversion in Serbian Film - Simić, Marina; Ničić, Miloš (Bulletin of the Institute of Ethnography SASA, 2022)
In this paper, we will discuss two issues. First, the relation between political theory and film studies is discussed as the basis for the emergence of critical film studies and its contemporary transformation. Second, we consider the kynical subversion and ironic appropriation as a set of frameworks for understanding the social reality and politics in the Yugoslav Black Wave cinema as well as in the movies of the contemporary Serbian cinematography. New forms of popular appropriations of cinematographic heritage show the ways through which both the very movies and critical film studies have disassociated themselves from Althusserian social critique and embraced contemporary ideas of kynical appropriation and irony as forms of social critique.